Representing Diversity or Lack-Thereof: An Analysis of College/University Health Science Education Program Websites. - Knettle, Mari; King, Rachel S.; Nowacki, Amy S.; Stoller, James K.; Patel, Pinal; Barbor, Naomi R. (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
Addressing lagging diversity among health professionals while seeking to fill high-demand positions will require health science education (HSE) programs to recruit students from currently underrepresented groups. This study evaluated the websites of programs in the most needed professions (n = 114) against 12 diversity metrics and across type of institution, degree levels, and disciplines. On average, each program met 2 criteria (range 0-10), and most of their websites (79%) showed > 1 image of an individual from an underrepresented group. Public college and degree-offering programs met more diversity metrics than the other categories assessed. All HSE programs, especially the most accessible, should seize opportunities to improve their presentation of diversity to recruit students from underrepresented groups.